A smart magnetically separable MIL-53(Al) MOF-coated nano-adsorbent for antibiotic pollutant removal with rapid and non-contact inductive heat regeneration - Thilina R. Katugampalage (Elsevier, 2021)
Metal-organic framework (MOF), MIL-53(Al), coated magnetic nanoparticles (MNP) were developed in this work for highly efficient adsorption and removal of an antibiotic pollutant oxytetracycline (OTC) from water. The adsorbed OTC molecules, which are heat labile, can be degraded rapidly using inductive heating which also regenerates the nano-adsorbent. Polyethylene glycol (PEG) coated MNP was used as a seed for growing the MIL-53(Al) MOF. The MIL-53(Al) coating was achieved via a facile green synthesis route using deprotonated terephthalic acid in an aqueous alkaline solution. The MIL-53(Al) coating layer on the MNP was found to have low crystallinity compared to that of the pristine MIL-53(Al) possibly due to the mismatch growth on the PEG-coated MNP surface. Nevertheless, the obtained nano-sorbent displays high OTC adsorption capacity of 794 mg/g at optimal pH 8. The adsorbed OTC on the nano-sorbent can be destructed using a rapid non-contact inductive heating of the magnetic core. Adsorption and regeneration were carried out up to 9 cycles in the presence of OTC. FTIR and PXRD shows that OTC adheres strongly to the MIL-53(Al) framework which causes gradual MIL-53(Al) degradation after several cycles of heat regeneration. Nevertheless, the MIL-53(Al) coated MNP without the adsorbed OTC shows strong structural integrity even after 9 regeneration cycles. The work demonstrates the high potential of the developed nano-sorbent for use in pollutant removal, magnetic separation of toxic pollutants as well as rapid regeneration of the nano-sorbents using induction heating.